Atlas of Brain and Spine Oncology Imaging - Karimi, Sasan; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Atlas of Brain and Spine Oncology Imaging presents a comprehensive visual review of pathologic disease variations of cancers of the brain and spine through extensive radiologic images. The focus of the book is on algorithmic strategies for identifying neoplastic pathologies commonly found in brain and spinal tumors through a visual representation of the variety of appearances that each neoplasm takes, within both benign and malignant manifestations. With contributions from radiologists on staff at a National Cancer Institute-designated comprehensive cancer center, who draw from an extensive collection of diagnostic images across all imaging modalities, this book will be valuable to practicing radiologists, radiation oncologists, surgeons and other practitioners involved in the diagnosis and treatment of brain and spinal neoplasms in all patient populations.
Adult Brain Tumors -- Pediatric Brain Tumors -- Sellar and Parasellar Masses -- Neoplastic Disease of the Spine.
Keywords: Medicine; Radiology, Medical; Oncology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Neuroradiology; Oncology